2019
DOI: 10.1002/nau.24065
|View full text |Cite
|
Sign up to set email alerts
|

Exploring biomarkers in the overactive bladder: Alterations in miRNA levels of a panel of genes in patients with OAB

Abstract: Aims It has been demonstrated that there are abundant stable microRNAs (miRNAs) in plasma, which is potentially disease‐specific. Adrenergic and muscarinic pathways play an important role in voiding physiology. Alterations in the levels of miRNAs are thought to influence the regulation of these pathways at the molecular level. The aim of this study was to investigate the relationship of miRNAs with overactive bladder pathogenesis and to provide a new perspective to treatment approaches. Methods This study incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…Contrary to expectations, patients showed lower GEF levels than controls, but the difference was not significant. Similar to this finding, in our previous study, the expression of miR-92a-3p, which is thought to inhibit GEF synthesis by targeting the gene responsible for GEF, was elevated in patients with OAB [14]. This observation supports the finding of lower GEF levels in OAB patients, and these data suggest that different factors may affect the regulation of ROCK2 in the detrusor muscle contraction mechanism in OAB.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Contrary to expectations, patients showed lower GEF levels than controls, but the difference was not significant. Similar to this finding, in our previous study, the expression of miR-92a-3p, which is thought to inhibit GEF synthesis by targeting the gene responsible for GEF, was elevated in patients with OAB [14]. This observation supports the finding of lower GEF levels in OAB patients, and these data suggest that different factors may affect the regulation of ROCK2 in the detrusor muscle contraction mechanism in OAB.…”
Section: Discussionsupporting
confidence: 90%
“…Elevated levels of ROCK2, which functions in the cholinergic pathway, may result in OAB symptoms as a result of increased contraction via increased ROCK2 activation in the bladder smooth muscle. In support of this finding, in our previous study, the expression of miR-139-5p, which is thought to inhibit ROCK2 synthesis by targeting the gene responsible for ROCK2, was found to decrease in patients with OAB [14]. In the current study, ROCK2 was also seen to have a significant potential relationship in the ROC curves (AUC = 0.651).…”
Section: Discussionsupporting
confidence: 84%
“…MicroRNAs are short, approximately 22 nucleotide long noncoding RNA molecules that can post-transcriptionally regulate gene expression. Various microRNAs can serve as biomarkers of different lower urinary tract diseases, such as bladder cancer [ 139 ], bladder outlet obstruction [ 140 ], overactive bladder [ 141 ], and IC/BPS [ 142 , 143 ], and they have also been recognized as emerging therapeutic targets. In the present review, we identified two studies trialing microRNAs as potential drug targets in animal models of IC/BPS.…”
Section: Resultsmentioning
confidence: 99%
“…These results were confirmed by the qRT-PCR findings. Recently, Fırat et al also reported that miR-139-5p was significantly downregulated in OAB patient plasma (7). Rho-associated coiled-coil-containing protein kinase 2 (ROCK2) was identified as a direct target of miR-139-5p and was effective in the ROCK2/myosin-light chain (MLC) and cholinergic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the combination of upregulated miR-98-5p and downregulated miR-139-5p in the plasm of patients' overactive bladder (OAB) was found to be a useful biomarker for OAB. However, no correlation was determined between the levels of miRs and OAB symptom score (7). Meanwhile, the above research only concentrated on finding the expression patterns of miRNA particularly in OAB patients.…”
Section: Original Articlementioning
confidence: 99%